PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (PADA SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017) - Eka Dela Oktiwiati; Mafizatun Nurhayati (Universitas Mercu Buana, 2020)
This study aims to determine the effect of Profitability, Capital Structur, and Investment Decision to company values. This population is pharmacist companies of Indonesia Stock Exchange on periode 2013 to 2017. The research design is causal research. The sampling technique is purposive sampling method. The method derived 6 companies that meet the criteria from 9 companies during the observation period of five years. Total sampel are 30 sample. The analysis technique used is the panel data regression. The results showed that profitability has positive and significant influence towards the firm value, while the capital structure has positive and significant towards the firm value. And the investment decision has positive and significant influence towards the firm value.